Discovery of 3, 5-substituted 6-azaindazoles as potent pan-Pim inhibitors. Issue 22 (15th November 2015) - Hu, Huiyong; Wang, Xiaojing; Chan, Grace Ka Yan; Chang, Jae H.; Do, Steven; Drummond, Jake; Ebens, Allen; Lee, Wendy; Ly, Justin; Lyssikatos, Joseph P.; Murray, Jeremy; Moffat, John G.; et al.
Graphical abstract: Abstract: Pim kinase inhibitors are promising cancer therapeutics. Pim-2, among the three Pim isoforms, plays a critical role in multiple myeloma yet inhibition of Pim-2 is challenging due to its high affinity for ATP. A co-crystal structure of a screening hit1 bound to Pim-1 kinase revealed the key binding interactions of its indazole core within the ATP binding site. Screening of analogous core fragments afforded 1 H -pyrazolo[3, 4- c ]pyridine (6-azaindazole) as a core for the development of pan-Pim inhibitors. Fragment and structure based drug design led to identification of the series with picomolar biochemical potency against all three Pim isoforms. Desirable cellular potency was also achieved.